Profiling Secondary Students’ Critical Thinking in Contextual Redox Learning through Video Storytelling - Nala Izzul Muna; Harjono (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2026)
Critical thinking is an essential competency in chemistry education; however, assessment in redox instruction often relies on conventional written tests that inadequately capture students’ contextual reasoning. This study aimed to profile secondary students’ critical thinking skills in environmentally contextualized redox learning through a video storytelling task. A quantitative descriptive cross-sectional design was employed involving 60 eleventh-grade students from a secondary school in Semarang, Indonesia. Data were collected through individual narrative videos explaining redox mechanisms within a hexavalent chromium (Cr⁶⁺) remediation scenario. Video transcripts were analysed using a four-level analytic rubric based on six critical thinking indicators: interpretation, analysis, inference, evaluation, explanation, and self-regulation. Descriptive statistics, polychoric correlation, and log-odds modelling were used to examine performance distribution, inter-indicator relationships, and relative cognitive demand. The findings revealed strong performance in explanation and inference, moderate performance in evaluation, and comparatively lower performance in self-regulation, which emerged as the most cognitively demanding dimension. These results indicate that critical thinking in contextual redox learning is multidimensional and hierarchically structured.